2008
DOI: 10.1166/jnn.2008.ic07
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Electrical Properties of Semiconducting ZnO Nanosheets

Abstract: ZnO nanosheets were fabricated by an oxygen-assisted carbothermal reduction process and their properties were evaluated. In particular, the FET characteristics and photoluminescence properties of ZnO nanosheets were evaluated. The conduction type of ZnO nanosheets was determined as an n-type and the mobility was 20-40 cm2/ V-s, which is fairly high compared to ZnO nanowires. This might be attributed to the wide conduction area of ZnO nanosheet compared to nanowire structures and their better crystallinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The most representative TMOs EEL is ZnO, which possesses several favorable physical properties including good transparency, high electron mobility, non-toxicity and low production cost. 46,47 ZnO is a n-type metal oxide with a LUMO and a HOMO energy level around À4.3 eV and À7.6 eV, respectively. The LUMO energy level of the commonly used electron acceptors (e.g., PC 61 BM and PC 71 BM) is about À4.3 eV, and the HOMO energy level of the electron donors is around À5.0 eV, indicating that ZnO is a good EEL and hole blocking layer in BHJ OPVs.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…The most representative TMOs EEL is ZnO, which possesses several favorable physical properties including good transparency, high electron mobility, non-toxicity and low production cost. 46,47 ZnO is a n-type metal oxide with a LUMO and a HOMO energy level around À4.3 eV and À7.6 eV, respectively. The LUMO energy level of the commonly used electron acceptors (e.g., PC 61 BM and PC 71 BM) is about À4.3 eV, and the HOMO energy level of the electron donors is around À5.0 eV, indicating that ZnO is a good EEL and hole blocking layer in BHJ OPVs.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…All these studies indicated that the performance of PSCs with an inverted device structure is sensitive to the interface between the ITO cathode and the active layer. Recently, zinc oxide (ZnO) has drawn much attention because it has a good transparency in the whole visible region and a good electron mobility. Moreover, the ZnO thin film can be easily deposited from corresponding solution via various solution processes, following thermal annealing treatment. All these features make ZnO an ideal material as a buffer layer for PSCs with an inverted device structure. , …”
Section: Introductionmentioning
confidence: 99%
“…Several chemical methods for the synthesis of ZnO in pure and even mixed with metal oxides have already been reported, a few of those methods like sol-gel [20,[27][28][29][30], hydro (solvo)-thermal [15][16][17][31][32][33][34][35][36][37], and some other works [38][39][40][41][42][43][44][45] on synthesis and application of ZnO nanostructures may be visited. Intensive research has been focused on fabricating one-dimensional ZnO nanostructures and in correlating their morphologies with their size-related optical and electrical properties [12, 15-17, 33, 37, 38].…”
Section: Introductionmentioning
confidence: 99%